Global estimates of the number of pregnancies at risk of malaria from 2007 to 2020: a demographic study. Issue 1 (January 2023) - Reddy, Valentina; Weiss, Daniel J; Rozier, Jennifer; ter Kuile, Feiko O; Dellicour, Stephanie
Summary: Background: The most recent global estimates of the number of pregnancies at risk of Plasmodium falciparum and Plasmodium vivax malaria infection are from 2007. To inform global malaria prevention and control efforts, we aimed to estimate the global distribution of pregnancies at risk of malaria infection from 2007 to 2020. Methods: We used estimates from the Malaria Atlas Project on the total population living in areas of P falciparum and P vivax transmission, combined with country-specific demographic data on women of reproductive age, fertility rates, induced abortions, and stillbirths, to derive the annual number of pregnancies overall, by parasite species, and by endemicity strata from 2007 to 2020. The definition of endemicity strata was based on the parasite point prevalence in individuals aged 2–10 years for P falciparum and 1–99 years for P vivax . We also did a sensitivity analysis in which we considered most of sub-Saharan Africa endemic for P vivax . Findings: In 2020, 121·9 million pregnancies occurred in malaria transmission areas, resulting in an estimated 70·9 million (58·1%) livebirths. The total number of pregnancies at risk of malaria was 52·9 million in the WHO South-East Asia (SEARO) region, 5·1 million in the Western Pacific (WPRO) region, 46·1 million in the Africa (AFRO) region, 11·1 million in the Eastern Mediterranean (EMRO) region, and 6·7 million in the Americas (AMRO) region. Between 2007 and 2020, pregnancies in areas of P falciparum transmission declined by 11·4% globally, despite an overall 7·0% increase in pregnancies, representing a decrease of 100·0% in the WHO Europe (EURO) region, 52·6% in WPRO, 51·5% in AMRO, 23·9% in EMRO, and 17·2% in SEARO, and a 25·4% increase in AFRO. Pregnancies in P vivax transmission areas fell by 42·8%, representing a decrease of 100·0% in EURO, 89·8% in WPRO, 48·4% in AMRO, 32·4% in EMRO, and 10·0% in SEARO, and a 25·8% increase in AFRO. Our sensitivity analysis suggests that the number of pregnancies at risk of P vivax infection could be seven-fold higher for AFRO if the whole of sub-Saharan Africa was considered endemic for P vivax . Interpretation: Between 2007 and 2020, substantial declines in the number of pregnancies at risk of malaria were seen globally. However, in AFRO, 25·4% more pregnancies were at risk of P falciparum or P vivax malaria than in 2007. This increase in the number at risk in AFRO comes despite the decline in malaria rates due to the rapidly rising population and the corresponding number of pregnancies in endemic areas. These estimates should guide priority setting for resource allocation to control malaria in pregnancy. Funding: Bill & Melinda Gates Foundation and Telethon Trust.